(untitled) (Tejganga Darpan, 2026)
This paper analyses the interrelation between knowledge discourses and educational justice via the theoretical perspectives of Paulo Freire’s critical pedagogy, Michel Foucault’s power-knowledge framework, and compatible awareness from Jurgen Habermas and Jack Mezirow. In the context of Nepal, the study scrutinises dual-medium instruction, scholarship policies, and environmental education as core areas where justice is both fostered and restricted. Using a conceptual and interpretive approach, the paper includes a global theoretical lens with local educational realities to investigate issues of inclusion, equity, empowerment, and justice as a whole. The outcomes in this study show that, although Nepal’s educational policies focus on inclusion, implementation is often bound by linguistic hierarchies, bureaucratic structures, and global-local tensions. In the context of Nepal, the study also argues that achieving educational justice demands epistemic inclusion, multilingual policies, critical pedagogy, transformative teacher education, decolonial approaches, participatory curriculum development, and greater recognition of indigenous knowledge systems.